The substitution financing effect of suppliers’ trade credit on customers’ trade credit in China - Guo, Chun; Su, Wunhong; Song, Xiaobao (Journal of Business Economics and Management, 2021)
This study investigates the substitution financing effect of suppliers’ trade credit on customers’ trade-credit using Chinese listed firms from 2009 to 2018. Results verify the substitution financing effect of suppliers’ trade credit on customers’ trade credit, indicating that firms with higher suppliers’ trade credit have lower customers’ trade credit. Moreover, suppliers’ trade-credit substitutes customers’ trade credit by alleviating financing constraints. Customer concentration weakens the substitution financing relation. Finally, the substitution financing effect of customers’ trade credit on bank credit is more pronounced than that of suppliers’ trade credit. As exogenous policy shock, the capital market liberalization has no significant impact on the substitution financing relation between heterogeneous trade credits. This study reveals that trade credit is heterogeneous rather than homogeneous. The substitution financing effect also exists in trade credit inside, which expands the existing literature’s understanding of trade credit and the substitution financing theory’s connotation.